Equilibrium and Mechanism of Removal of Total Dissolved Solids and Hardness by Adsorption onto Neem Seed Powder Adsorbent - Urooj Gul Sandilo, Urooj Gul Sandilo; Amir Detho, Amir Detho; Asif Ali Memon, Asif Ali Memon; Abdul Qayoom Jakhrani, Abdul Qayoom Jakhrani; Abdul Kadir, Aeslina (Springer, 2023)
This study is aimed to investigate the level of total dissolved solids and hardness of groundwater using neem seed powder as an adsorbent. Analysis of four groundwater samples in triplicate has been collected from diferent locations in Nawabshah city. The level of total dissolved solids (TDS), hardness, calcium, and magnesium is examined using seven diferent doses, i.e., 0.5,1.0 1.5, 2.0, 2.5, 5.0, and 10.0 g of neem seed powder per 100 ml of groundwater samples. The neem seed powder is mixed with groundwater samples and then stirred for a few minutes for amalgamation. The samples subsequently are left without disturbance for 30 min. The level of total dissolved solids has been measured with a TDS meter, hardness, and calcium using the titration method and magnesium with a different method. It was from the analysis that the removal percentage achieved 70% of total dissolved solids, 70% of hardness, 62% of calcium, and 65% of magnesium reduced from the examined groundwater samples. The maximum reduction of TDS, hardness, and calcium magnesium is achieved using the dose of 2.5 g/100 mL of groundwater samples at a retention time of 30 min. However, the fnding result revealed that the values of the coefcient of determination (R2 ) for Langmuir are higher than Freundlich, indicating that better ftted than the latter. The R2 results showed that TDS, hardness, calcium, and magnesium removal were 0.9972, 0.9953, 0.9961, and 0.9958, respectively. This indicates that adsorbent surface covers a monolayer of adsorbing molecules.